Transition from Herodotus to Plutarchus World: Pathology of Persian Translations of Classical Texts - Esmaeil Sangari (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
In the studies related to Ancient Iran, the lack of data including classical historians’ texts, parchments, inscriptions, as well as thearcheological and literary evidence documents make the historians face problems in analyzing precisely. Translation of a classical work related to a special period has an importance that the historical data will be interpreted in other ways. Thus, it is clear that translation of classical Greek and Latin works have double importance. In addition to a complete focus on the historical period of the text, it is worthwhile to see that the translator tries to be completely loyal to the text with a full knowledge of author’s style. In this research, it aims to give the ways in order to prevent translator and researcher’s mistakes by comparative studies of two ancient historians from ancient Greece and Rome, Herodotus Halicarnassus and Plutarchus Chaeronea.